Comparative evaluation of retention, cariostatic effect and discoloration of conventional and hydrophilic sealants - A single blinded randomized split mouth clinical trial - Jayashri Prabakar; Joseph John; I Meignana Arumugham; R Pradeep Kumar; D Srisakthi (Wolters Kluwer Medknow Publications, 2018)
Introduction: Pit and fissures are approximately eight times vulnerable than the smooth surface caries lesion. Sealants are effective in preventing, arresting, and progression of pit-and-fissure occlusal caries lesions. The failure of sealant resin-based retention is mainly attributed to the moisture contamination. To overcome this drawback, UltraSeal XT® hydro, a moisture-friendly sealant, has been introduced. Aim: This study aimed to compare and evaluate the retention, cariostatic effect, and discoloration of conventional Clinpro™ 3M™ ESPE™ and hydrophilic UltraSeal XT® sealants among 12 to 15-year-old schoolchildren for 3 months. Materials and Methods: A single-blinded, randomized, split-mouth clinical trial was conducted among thirty schoolchildren aged 12-15 years. Sealants used in the present study were Group I - Clinpro™ and Group II - UltraSeal XT® hydro. Sealants were provided in the school by two operators based on the computer-generated random sequence and the study participants were evaluated after 3 months for sealant coverage, caries incidence, and discoloration using Color, Coverage and Caries sealant evaluation system. Sealant coverage between the two sealants was compared using Mann-Whitney U-test and Z-test for proportions. Results: A total of 47 teeth (78.3%) with UltraSeal XT® Hydro had the sealant covering in all the fissures compared to Clinpro™ 3M™ ESPE™ which was 46.7% (28 teeth) and the difference was observed to be statistically significant. Conclusion: Hydrophilic UltraSeal XT® Hydro yielded better sealant coverage (retention) compared to the conventional Clinpro™ 3M™ ESPE™. No difference was observed with regard to cariostatic effect and discoloration.